A Decision Support System for Evaluation Service Quality by Fuzzy SERVQUAL: A Case Study of a Modern Riteil - Juriyah Ayu; Deswita Sri Yani (Jurnal Riset Ilmu Teknik, 2023)
This research was conducted in a retail store in the city of Semarang. The main focus was to measure the quality of service against consumer perceptions and expectations of the retail rate. This study analyses the factors influencing consumer perception and how to design services to match consumer expectations. The population in this study is consumers who shop. The method used in this study is the Fuzzy Servqual method. Based on the results of processing and analysis, it is known that the dimensions that have the highest gap value are the Assurance dimension (-1.5175), while the tangibles dimension (-1.37), reliability (-0.318), responsiveness (-0.176) and empathy (0.315). From the result of the gap value, the empathy dimension is very satisfying, and customers feel comfortable with employee service, friendliness, and assistance with product info at retail. The assurance dimension is a dimension that must be improved by improving the state of the room, temperature, and lighting and providing a safe area for retail protesters.